Comparação da IDGA, ELISA e nested PCR no diagnóstico da anemia infecciosa eqüina em eqüinos, Asininos e Muares. - Pedro Moreira Couto Motta (2007)
A lot of studies about horses (Equus caballus) immune responses to equine infectious anemia virus (EIAV) have been done all over the world, but there are little information concerning immune responses of mule (Equus caballus X Equus asinus) and donkey (Equus asinus) to natural infection with EIAV. The aim of this work was to compare the serological and virus detection in asinus, mules and equines naturally infected with EIAV, and evaluate the importance of mules and asinus to maintain the EIAV in the Brazilian herds. In the present study sera and peripheral blood mononuclear cells (PBMC) samples were collected of 124 horses, 119 mules and 75 asinus, in a total of 318 samples. DNA of PBMC was extracted from 114 horses, 79 mules and 35 asinus. All samples were tested by Agar Gel Immunodiffusion (AGID) and Enzyme-linked Immunosorbent Assay (ELISA). DNA was submitted to nested polymerase chain Reaction (nPCR). The correlation to AGID and ELISA for equines was better than mules. The same was observed between AGID and nPCR. When the correlation between ELISA and nPCR was compared, the best correlation was observed in equines again. The number of asinus was not significant to statistic evaluation but results showed that 10 negative asinus in AGID were positive in ELISA and 7 were positive in nPCR. Two positive asinus in AGID were positive in ELISA and nPCR. These results showed that serological responses and virus detection in mules might be different from the responses in equines. The concordance between AGID, ELISA and PCR tests were better in equine than in mules.